International Financial Policy : Essays in honor of Jacques J. Polak. (International Monetary Fund, 1991)
During his distinguished career at the IMF, Jacques J. Polak served as both Director of Research and, subsequently as a member of the IMF Executive Board. His distinct contribution to the discipline of international financial policy is highlighted in this book edited by Jacob A. Frenkel and Morris Goldstein. The papers included were prepared for a conference, cosponsored by the Netherlands Bank and the IMF, held in Polak's honor in Washington, D.C., in January 1991.